Perilipin 3 promotes the formation of membrane domains enriched in diacylglycerol and lipid droplet biogenesis proteins - Khaddaj, Rasha; Stribny, Jiri; Cottier, Stéphanie; Schneiter, Roger (Frontiers in Cell and Developmental Biology, 2023)
Lipid droplets (LDs) serve as intracellular stores of energy-rich neutral lipids. LDs form at discrete sites in the endoplasmic reticulum (ER) and they remain closely associated with the ER during lipogenic growth and lipolytic consumption. Their hydrophobic neutral lipid core is covered by a monolayer of phospholipids, which harbors a specific set of proteins. This LD surface is coated and stabilized by perilipins, a family of soluble proteins that specifically target LDs from the cytosol. We have previously used chimeric fusion proteins between perilipins and integral ER membrane proteins to test whether proteins that are anchored to the ER bilayer could be dragged onto the LD monolayer. Expression of these chimeric proteins induces repositioning of the ER membrane around LDs. Here, we test the properties of membrane-anchored perilipins in cells that lack LDs. Unexpectedly, membrane-anchored perilipins induce expansion and vesiculation of the perinuclear membrane resulting in the formation of crescent-shaped membrane domains that harbor LD-like properties. These domains are stained by LD-specific lipophilic dyes, harbor LD marker proteins, and they transform into nascent LDs upon induction of neutral lipid synthesis. These ER domains are enriched in diacylglycerol (DAG) and in ER proteins that are important for early steps of LD biogenesis, including seipin and Pex30. Formation of the domains in vivo depends on DAG levels, and we show that perilipin 3 (PLIN3) binds to liposomes containing DAG in vitro. Taken together, these observations indicate that perilipin not only serve to stabilize the surface of mature LDs but that they are likely to exert a more active role in early steps of LD biogenesis at ER subdomains enriched in DAG, seipin, and neutral lipid biosynthetic enzymes.